The Appalachian Regional Commission : twenty-five years of government policy - Bradshaw, Michael J. (Michael John), 1935- (University Press of Kentucky, 1992)
The images of poverty in Appalachia that John F. Kennedy used in his campaign for the presidency in 1960 shocked and disturbed many Americans. Five years later, President Lyndon Johnson and the U.S. Congress demonstrated their commitment to that neglected and exploited region with the creation of the Appalachian Regional Commission. In this insightful book, Michael Bradshaw explores the ARC's unique federal-state partnership and analyses in detail the contributions of the local development districts. But this work is more than an analysis of a government agency; it is, as Bradshaw notes,